2021
DOI: 10.1155/2021/8560668
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Detection and Analysis of Perfusion Pressure through Measuring Oxygen Saturation and Requirement of Dural Incision Decompression after Laminectomy

Abstract: Background. Traumatic spinal cord injury (SCI) can continue and transform long after the time of initial injury. Preventing secondary injury after SCI is one of the most significant challenges, and early intervention to return the blood flow at the injury site can minimize the likelihood of secondary injury. Objective. The purpose of this study is to investigate whether laminectomy can achieve the spinal cord blood flow by measuring the spinal blood oxygen saturation intraoperatively without the presence of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%